Juridical Review of Foreign Land Ownership in Indonesia Under Government Regulation No. 18 of 2021 on Management Rights, Land Rights, Apartment Units, and Land Registration - Zhakiah Putri; Yuniar Rahmatiar; Muhamad Abas (Warmadewa Press, 2025)
This study aims to analyze the implications of Government Regulation No. 18 of 2021 on Management Rights, Land Rights, Apartment Units, and Land Registration concerning foreign nationals and to examine the legal certainty of foreign land ownership under the Investment Law (PMA) and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). The study highlights inconsistencies in the regulation regarding foreign land ownership, revealing ambiguities in the substantive provisions of Government Regulation No. 18 of 2021. Several articles in this regulation conflict vertically with the Job Creation Law and the Basic Agrarian Law. Consequently, for legal certainty, the government must evaluate and restructure the relevant provisions. Despite strict restrictions on foreign land ownership, certain legal loopholes enable foreigners to acquire land rights through specific agreements. This research employs a normative juridical methodology. Government Regulation No. 18 of 2021 allows foreigners to obtain land rights under the status of Right to Build (Hak Guna Bangunan – HGB), provided they hold a residence permit in Indonesia. Additionally, the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) plays a crucial role in ensuring the administrative processes related to land ownership and use by foreign nationals and foreign investment companies comply with legal provisions.